MEMBANGUN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL BENTHIK - Fikri, Tsaqibul; Nimah, Roudlotun; Dewi, Rosiani (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2021)
Rapid technological advances have also influenced children's play activities. Modern impression of digital games is not only attached to the equipment used when playing, but also how to play it. Digital games are carried out in a comfortable room because in general air-conditioning such as internet cafes or timezone (rides to play) which causes a lack of physical movement of children. Lack of physical movement can result in a lack of development of motor skills of children. This also happened to Raudlatul Athfal Naja Ali Tambakwatu's children who preferred to play using their cellphones alone rather than playing with friends. This study aims to determine the effect of traditional benthic games on gross motor skills in Raudlatul Athfal Naja Ali Tambakwatu's children who have been mostly affected by digital games. This study uses a quantitative approach with non-parametric statistics with a sample of 15 children. Data collection is done by observation and documentation techniques. The results showed that: (1) gross motor skills in Raudlatul Athfal Naja Ali focused on worship activities, (2) Raudlatul Athfal Naja Ali children who initially did not know how to play benthic games made it a learning theme, and (3) traditional games benthik has a significant influence on the development of gross motor skills in Raudlatul Athfal Naja Ali.